Top Up of Ongoing Murabahah Financing for Customers of Astra Credit Companies (ACC) Banda Aceh from The Perspective of Sharia Economic Law - Eriyanti, Nahara (TAWAZUN: Journal of Sharia Economic Law, 2024)
Astra Credit Companies (ACC) in Banda Aceh provides an ongoing top up service for murabahah financing, which is an increase in the value of financing. There are allegations that the ACC top up service system raises the practice of loan interest in the form of usury. So the problem studied in this research is how the Sharia Economic Law review of the top up customer eligibility assessment system? This research was conducted with a conceptual approach, with the type of normative juridical research. Research data comes from the field and literature, namely through interviews, documentation studies, library materials. The result of the research is that the assessment and eligibility system for top up customers in murabahah financing products that are still ongoing at ACC Banda Aceh is carried out by assessing the customer's profile on the one hand and the number of customer instalments on the other. The aspects assessed are the positive customer profile of the customer smoothly paying, the number of principal debt instalments approaching repayment. According to the perspective of Sharia Economic Law, the assessment system and the eligibility of top up customers in murabahah financing products that are still ongoing at Astra ACC Banda Aceh so far have not fully fulfilled sharia principles. The problem that arises is the use and realisation of the contract in the top up service appears to use a debt and credit contract with interest which is considered usury. Therefore, ACC companies should avoid the practice of interest.